Personsentrert omsorg i praksis: Fire perspektiver på støttekontakttjenesten i demensomsorgen - en case studie design - Johannessen, Aud; Thorsen, Kirsten (Nordisk tidsskrift for helseforskning, 2018)
The number of people with dementia is increasing rapidly and will result in a growing demand for varied health and social services. Support contact is a potential service with positive implications, but it has yet to be explored fully. The aim of this study was therefore, to explore these questions: 1) Will the support contact service be a favorable service for people with dementia? 2) How is the service experienced by patients with dementia, their carers, the support contacts, and the municipality’s administration of the service? 3) What experiences do those involved have of the service, and what do they regard as essential for a good service? A case-study design with qualitative studies of the involved illustrates the concept. The study concludes that support contact can be a highly appropriate service for people with dementia and their carers, and eventually can be coordinated with other services.